Simulation in nursing baccalaureate courses of Brazilian educational institutions - Eduardo Fuzetto Cazañas; Rosana Leal do Prado; Tayomara Ferreira Nascimento; Silvia Franco da Rocha Tonhom; Maria José Sanches Marin (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: to characterize simulation practices in nursing courses in Brazil, considering the attributes developed, facilities, and challenges encountered. Methods: this is a cross-sectional and descriptive study, with a quantitative approach. Ninety-one coordinators of undergraduate courses participated in the study. An electronic questionnaire was used with open- and closed-ended questions. Results: the most used simulation modality is Specific Skills. Private courses and courses with integrated curricula most often use High Fidelity Simulation. Understanding the mobilization of affective attributes is still insufficient. Conclusion: it is important that undergraduate course managers are aware and take ownership of the elements that permeate simulation and invest to create a favorable environment for its effectiveness.